Analisis Kesalahan Siswa Dalam Menyelesaikan Soal pada Materi Persamaan Kuadrat - Grace Lisurara’ Sura’1; Suradi Tahmir; Awi Dassa (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2021)
This study aims to describe students’ errors in solving questions of quadratic equation. This research type is descriptive research using qualitative approach. The subject of this research is 3 students of grade XI SMK Negeri in Makassar who were selected based on the number of errors experienced in solving questions of quadratic equation. Data collection techniques used in this study is diagnostic test and interview methods then through three stages of data analysis namely data reduction, data presentation, and conclusion. The results obtained that the types of errors experienced by students in solving quadratic equation included conceptual error, principle error, and calculation error. This was because the low of students’ prerequisite knowledge about number operations, students didn’t understand about finding the roots of quadratic equation by completing the perfect square, students didn’t understand the abc formula to finding the roots of quadratic equation, and students inaccurate using arithmetic operations.